2005
DOI: 10.1038/sj.cdd.4401818
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of glutaredoxin-1 and thioredoxin-1 in β-amyloid toxicity and Alzheimer's disease

Abstract: Strong evidence indicates oxidative stress in the pathogenesis of Alzheimer's disease (AD). Amyloid b (Ab) has been implicated in both oxidative stress mechanisms and in neuronal apoptosis. Glutaredoxin-1 (GRX1) and thioredoxin-1 (TRX1) are antioxidants that can inhibit apoptosis signalregulating kinase (ASK1). We examined levels of GRX1 and TRX1 in AD brain as well as their effects on Ab neurotoxicity. We show an increase in GRX1 and a decrease in neuronal TRX1 in AD brains. Using SH-SY5Y cells, we demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
130
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(142 citation statements)
references
References 39 publications
(63 reference statements)
9
130
1
2
Order By: Relevance
“…Grx1 resides mainly in the cytosol, although it may translocate into the nucleus in response to certain stimuli. For example, in the brains of patients with Alzheimer disease, control samples revealed Grx1 was located mainly in the cytosolic compartment, contrary to the nuclear staining in Alzheimer disease neurons (16). In our study nuclear translocation of Grx1 was evident in FAP salivary glands (indicated by arrows in Figure 2).…”
Section: Tissue Markers For Oxidative Stressmentioning
confidence: 59%
See 2 more Smart Citations
“…Grx1 resides mainly in the cytosol, although it may translocate into the nucleus in response to certain stimuli. For example, in the brains of patients with Alzheimer disease, control samples revealed Grx1 was located mainly in the cytosolic compartment, contrary to the nuclear staining in Alzheimer disease neurons (16). In our study nuclear translocation of Grx1 was evident in FAP salivary glands (indicated by arrows in Figure 2).…”
Section: Tissue Markers For Oxidative Stressmentioning
confidence: 59%
“…Despite the importance of Grx1 and Trx1 as regulators of oxidative stress and apoptosis, their role in FAP is completely unknown. We believe that overexpression of Grx1 may have a protective role, acting to detoxify FAP tissues as it does the frontal cortex and hippocampal neurons of the brain in Alzheimer disease (16). Trx1 was not up-regulated in the analyzed tissues with TTR deposition, except for DRG, probably because salivary glands and stomach mucosa are in contact with multiple stimuli and irritations.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…142 Accordingly, GRX1 overexpression protects against amyloid b-induced toxicity. 143 PD progression is associated with a depletion of GSH levels and an increase in ROS formation in the substantia nigra. In fact GSH depletion has been proposed as one of the early biochemical events associated with neuronal apoptosis in PD.…”
Section: Gsh Apoptosis and Disease Progressionmentioning
confidence: 99%
“…The antioxidant defenses include vitamins, minerals, and the antioxidant enzymes glutathione, superoxide dismutase, hydrogen peroxidase, catalase, and thioredoxins (8). The protection of thioredoxin 1 (TRX1) 1 against retinal photooxidative damage (9) and its role in neurodegenerative diseases like Alzheimer disease are known (10,11). TRX1, the substrate of thioredoxin reductase, can protect neuronal cells by scavenging free radicals, binding and inhibiting apoptosis signal-regulating kinase 1 (12), regulating transcription factors, and maintaining redox homeostasis (13).…”
mentioning
confidence: 99%